Alternatif penyelesaian sengketa asuransi melalui Badan Mediasi Asuransi Indonesia (BMAI) - Chandra Dewi Puspitasari (Jurnal Civics: Media Kajian Kewarganegaraan, 2007)
Insurance began to interest the public as a wqy to transfer risk. The important thing is that people should be able to choose health insurance companies (solvent), a reasonable premium rate, a good investment performance (Liquid, safe, and productive), to pay claims on time, do not make poliry holders, to report correctfy and on time, and did not violate an existing report. In practice, disputes often arise between the insurer and the insured Disputes can be resolved through Indonesian Insurance Mediation Board (BMAI). BMAI dispute settlement through the mediation process begins with. if the mediation process fails, will proceed to the level of aqjudication. In addition, if the insured can not accept the decision at the aqjudication level, so that he can bring the dispute to arbitration or court. But besides these advantages, BMAI also not free from some weaknesses. However, their presence is still needed to be one of the alternative dispute resolution insurance agencies in Indonesia.